Changes in self‐efficacy, collective efficacy and patient outcome following interprofessional simulation training on postpartum haemorrhage. Issue 19 (12th March 2017) - Egenberg, Signe; Øian, Pål; Eggebø, Torbjørn Moe; Arsenovic, Mirjana Grujic; Bru, Lars Edvin
Abstract : Aims and objectives: To examine whether interprofessional simulation training on management of postpartum haemorrhage enhances self‐efficacy and collective efficacy and reduces the blood transfusion rate after birth. Background: Postpartum haemorrhage is a leading cause of maternal morbidity and mortality worldwide, although it is preventable in most cases. Interprofessional simulation training might help improve the competence of health professionals dealing with postpartum haemorrhage, and more information is needed to determine its potential. Design: Multimethod, quasi‐experimental, pre–post intervention design. Methods: Interprofessional simulation training on postpartum haemorrhage was implemented for midwives, obstetricians and auxiliary nurses in a university hospital. Training included realistic scenarios and debriefing, and a measurement scale for perceived postpartum haemorrhage‐specific self‐efficacy, and collective efficacy was developed and implemented. Red blood cell transfusion was used as the dependent variable for improved patient outcome pre–post intervention. Results: Self‐efficacy and collective efficacy levels were significantly increased after training. The overall red blood cell transfusion rate did not change, but there was a significant reduction in the use of ≥5 units of blood products related to severe bleeding after birth. Conclusion: The study contributes to new knowledge on how simulation training through mastery and vicarious experiences, verbal persuasion and psychophysiological state might enhance postpartum haemorrhage‐specific self‐efficacy and collective efficacy levels and thereby predict team performance. The significant reduction in severe postpartum haemorrhage after training, indicated by reduction in ≥5 units of blood transfusions, corresponds well with the improvement in collective efficacy, and might reflect the emphasis on collective efforts to counteract severe cases of postpartum haemorrhage. Relevance to clinical practice: Interprofessional simulation training in teams may contribute to enhanced prevention and management of postpartum haemorrhage, shown by a significant increase in perceived efficacy levels combined with an indicated reduction of severe postpartum haemorrhage after training.